66 The contribution of adverse childhood experiences to post-injury psychological outcomes in urban black men in the US. (9th June 2015) - Therese, S Richmond; Adams, Nancy Kassam; Wiebe, Douglas; Rich, John; Reilly, Patrick; Shults, Justine
Abstract : Statement of purpose: To examine whether adverse childhood experiences (ACEs) contribute to severity of PTSD and depression symptoms after recent serious injury in Black men. Methods/approach: Injured Black adult men were consecutively enrolled during hospitalisation for an acute, serious injury. Baseline data, including demographics and injury-related characteristics, were collected during interviews conducted in hospital. A questionnaire assessed whether seven Adverse Childhood Experiences had been experienced prior to the age of 18 years. Primary outcomes were collected at 3 months post-discharge during an in-person interview using the PTSD Checklist (PCL-C) for PTSD symptom severity and the Quick Inventory of Depressive Symptoms-Self Report (QID-SR) for depression symptom severity. Results: 231 men (mean age = 37 years, SD = 15.8) were included in this analysis. Injury was classified as unintentional (52%) or intentional (48%, i.e. the result of interpersonal violence). Mean number of ACEs was 2.51; 83% reported at least 1 ACE and 37.7% reported >4. No association was found between number of ACEs and whether the index injury was intentional versus unintentional. Intentional injuries were associated with higher mean PCL-C scores (42.8 vs. 33.6, p < 0.0001) and higher mean QID-SR scores (10.0 vs. 8.0, p < 0.01). In adjusted multiple regression, younger age, intentional injury, and number of ACEs were independently associated with higher PCL-C scores. Intentional injury and number of ACEs were independently associated with higher QID-SR scores. Conclusions: This sample of urban Black men reported substantial histories of childhood trauma and adversity. There is a dose response relationship with higher numbers of ACEs contributing to more severe symptoms of PTSD and depression after serious traumatic injury. Significance and contributions: To improve outcomes after serious injury in urban Black men, previous trauma histories should be obtained and drive care practices that are trauma-informed. Funder: NINR R01NR013503